High Photon Upconversion Efficiency with Hybrid Triplet Sensitizers by Ultrafast Hole‐Routing in Electronic‐Doped Nanocrystals. Issue 37 (6th August 2020) - Ronchi, Alessandra; Capitani, Chiara; Pinchetti, Valerio; Gariano, Graziella; Zaffalon, Matteo L.; Meinardi, Francesco; Brovelli, Sergio; Monguzzi, Angelo
Abstract: Low‐power photon upconversion (UC) based on sensitized triplet–triplet annihilation (sTTA) is considered as the most promising upward wavelength‐shifting technique to enhance the light‐harvesting capability of solar devices. Colloidal nanocrystals (NCs) with conjugated organic ligands have been recently proposed to extend the limited light‐harvesting capability of molecular absorbers. Key to their functioning is efficient energy transfer (ET) from the NC to the triplet state of the ligands that sensitize free annihilator moieties responsible for the upconverted luminescence. The ET efficiency is typically limited by parasitic processes, above all nonradiative hole‐transfer to the ligand highest occupied molecular orbital (HOMO). Here, a new exciton‐manipulation approach is demonstrated that enables loss‐free ET by electronically doping CdSe NCs with gold impurities that introduce a hole‐accepting intragap state above the HOMO energy of 9‐anthracene acid ligands. Upon photoexcitation, the NC photoholes are rapidly routed to the Au‐level, producing a long‐lived bound exciton in perfect resonance with the ligand triplet. This hinders hole‐transfer leading to ≈100% efficient ET that translates into an upconversion quantum yield as high as ≈12% (≈24% in the normalized definition), which is the highest performance for NC‐based upconverters based on sTTA to date and approaches the record efficiency of optimized organic systems. Abstract : Semiconductor nanocrystals doped with electronic impurities are proposed as triplet sensitizers in photon upconversion assisted by triplet–triplet annihilation (TTA). Upon photoexcitation, the nanocrystals' photoholes are routed to a long‐living, impurity‐related state in resonance with the capping ligands' triplet. This results in 100% efficiency in triplet sensitization and leads to the highest upconversion quantum yield ever achieved for nanocrystal‐based TTA upconverters.